Medical doctors in health reforms a comparative study of England and Canada - Denis, Jean-Louis 1957-; Germain, Sabrina ca. 20./21. Jh; Régis, Catherine 1976-; Veronesi, Gianluca ca. 20./21. Jh (Sociology of health professions, 2022)
Health and legal experts from England and Canada consider the influence of medical doctors on reforms in this comparative study. With reflections on participation since the inception of publicly funded healthcare systems, they show how the status of doctors affects change